Trauma-induced heterotopic bone formation and the role of the immune system: A review. Issue 1 (January 2016) - Kraft, Casey T.; Agarwal, Shailesh; Ranganathan, Kavitha; Wong, Victor W.; Loder, Shawn; Li, John; Delano, Matthew J.; Levi, Benjamin
Abstract : ABSTRACT: Extremity trauma, spinal cord injuries, head injuries, and burn injuries place patients at high risk of pathologic extraskeletal bone formation. This heterotopic bone causes severe pain, deformities, and joint contractures. The immune system has been increasingly implicated in this debilitating condition. This review summarizes the various roles immune cells and inflammation play in the formation of ectopic bone and highlights potential areas of future investigation and treatment. Cell types in both the innate and adaptive immune system such as neutrophils, macrophages, mast cells, B cells, and T cells have all been implicated as having a role in ectopic bone formation through various mechanisms. Many of these cell types are promising areas of therapeutic investigation for potential treatment. The immune system has also been known to also influence osteoclastogenesis, which is heavily involved in ectopic bone formation. Chronic inflammation is also known to have an inhibitory role in the formation of ectopic bone, whereas acute inflammation is necessary for ectopic bone formation.